Psychological Dimensions and Textual Formation in the Poetry of Waddah Al-Yaman - Yasser, Dr.shaymaa Joda (Thi Qar Arts Journal, 2025)
The psychological dimensions in literary texts, both poetry and prose, reveal aspects of the state experienced by the author. By approaching and touching upon these dimensions, we can highlight some of the motives and reasons that led the poet to express the state they are in. This is where its importance in Arab and Western literary criticism stems from, as it has garnered the attention of critics and scholars throughout various stages until it settled into a comprehensive direction known as psychological criticism in text analysis. Despite its completeness, it must be integrated with the means that shaped the identity of the text and contributed to its production, including the mechanism of textual formation in poetry, which the research addresses in the poetry of Waddah Al-Yaman due to the scarcity of studies that have tackled it and the importance of the topics he composed. This research aims to shed light on the poet and the psychological features in his poetry and the role of textual formation in it.The psychological dimension, or what is known as the psychological aspect, is one of the dimensions through which literary works are studied. This dimension has gained significant popularity in the field of literature. However, some critics have objected to this dimension. Those advocating for the psychological dimension see the author, especially the poet, as capable—unlike ordinary people—of recalling their experience while maintaining their balance and calmness.On the other hand, those who object to the psychological dimension view it as an infringement on the literary text and a transgression of its artistic dimensions. The psychological interest in Arabic poetry is evident, as we find echoes of psychological analyses of ancient Arabic poetry in many studies. However, these studies have focused on the structure of the elegy and remained captive to the general psychological perspective.